A Tale of Two Cities and the Diaspora Therein: Portuguese New Christians between Rome and Pisa (1542‑1609) - James W. Nelson Novoa (Diasporas: Circulations, Migrations, Histoire)
The article deals with relations between Portuguese New Christians in Rome and Pisa between 1542 and 1609. While they were often united by ties of kinship and commercial interests, belonging to the Western diaspora of descendants of Jews from Portugal who adopted Christianity at the end of the 15th century, they were very different based on the two locales and their ways of being in the world. While their presence is Rome predated that of Pisa and their arrival in the Tuscan city was, in fact, organised from Rome, by the end of the 16th century they were able to constitute an important, especially mercantile community in Pisa and Livorno. The possibility offered to New Christians to openly embrace Judaism allowed for the establishment of a Portuguese Jewish community in Tuscany, unhindered by the constraints of a ghetto, completely unlike the situation in Rome